Analysis of Consumer Perspectives on the Use of LRT (Light Rail Transit) Palembang - Ovellya Hartami Darmawan; hamid Halin; Muhammad Wadud (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This research aims to determine consumer perspectives regarding the use of LRT (Light Rail Transit) Palembang, data collection techniques were obtained from observational research, interviews and questionnaires. To make the initial steps of SWOT analysis and make decisions, this data collection technique uses questionnaire data collection of 130 samples, which form each SWOT variable. The results of the data analysis of the internal factor value, namely 3.89, were obtained from the total sum of the company's strength and weakness factor ratings. A value of 3.89 means that the value is high according to the Likert scale assessment. The highest strength value is found in the point of complete, safe and comfortable business facilities for business continuity with a weight of 3.75 which shows that LRT facilities have a big influence on business and the highest weakness value is found in the point that route coverage has not been fully detected in the Palembang area with a weight of 3.57. Meanwhile, the data analysis value of the external factor value is 3.13, which means that the value is high according to the Likert scale assessment, and the highest opportunity value is found at the passenger target point which will continue to increase with a weight of 3.61, which shows that the company is able to maximally capture market share. and supported by high purchasing power, while the low opportunity value is found at the point of development of the LRT network connecting the city of Palembang with a weight of 3.55, the lowest threat value is at the point where people prefer to use private vehicles with a weight of 3.26.